Comunicación multimedia en el proceso de enseñanza y aprendizaje en los estudiantes de la carrera de Comunicación de la Universidad Técnica Babahoyo Extensión Quevedo - De Loor Ayala, Leila Johana (2021)
The present research work developed called: multimedia communication in the process of teaching and learning in the students of the career of communication of the technical university Babahoyo extension Quevedo where the programs or platforms within the multimedia communication affect the students making difficult the process of teaching and learning, causing a low academic performance in them. The main objective of this research work is to determine the types of multimedia communication used in the teaching and learning process in university students of the communication career. The study included the collection of documentary information based on scientific journal articles, theses, books, among others. In addition, to carry out the research development, the respective multiple-choice survey directed to university students was conducted to obtain the definitive results of the application of the survey, it was determined that the access of certain programs or virtual platforms is problematic because the program adapted to a computer is different from that of a mobile device. The study included the collection of documentary information based on scientific journal articles, theses, books, among others. In addition, to carry out the research development, the respective multiple-choice survey directed to university students was conducted to obtain the definitive results of the application of the survey, it was determined that the access of certain programs or virtual platforms is problematic because the program adapted to a computer is different from that of a mobile device. Likewise, within the situations detected, the programs or virtual platforms are detailed, which makes it difficult for many students, as well as in the solutions proposed, an instruction guide is presented to be able to access properly without having complications in learning in the educational area at the time of performing their academic activities. The purpose of this project is to encourage students of the communication career and at the same time to motivate them to access virtual programs with the respective instructions of the management of the same and facilitate the process of teaching and learning in university students.